2020
DOI: 10.3390/ijms22010212
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Metabolite Tetrahydrocurcumin in the Treatment of Eye Diseases

Abstract: Curcumin is one of the most valuable natural products due to its pharmacological activities. However, the low bioavailability of curcumin has long been a problem for its medicinal use. Large studies have been conducted to improve the use of curcumin; among these studies, curcumin metabolites have become a relatively new research focus over the past few years. Additionally, accumulating evidence suggests that curcumin or curcuminoid metabolites have similar or better biological activity than the precursor of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…However, there is a lack of consensus among ophthalmologists and researchers on the interest of nutritional supplements containing antioxidant vitamins, carotenoids, trace elements and/or ω3 PUFAs in ophthalmology. Dry eye disease [14][15][16], myopia complications and progression [72], cataracts [32,73], or sightthreatening diseases such as glaucoma, DR, and AMD [16][17][18][19][20][21]32,[74][75][76][77][78][79], have been important targets of antioxidants and ω3 PUFAs. DHA is an essential structural constituent of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of consensus among ophthalmologists and researchers on the interest of nutritional supplements containing antioxidant vitamins, carotenoids, trace elements and/or ω3 PUFAs in ophthalmology. Dry eye disease [14][15][16], myopia complications and progression [72], cataracts [32,73], or sightthreatening diseases such as glaucoma, DR, and AMD [16][17][18][19][20][21]32,[74][75][76][77][78][79], have been important targets of antioxidants and ω3 PUFAs. DHA is an essential structural constituent of cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies involving Ahr −/− mice, while Ahr −/− mice developed severe cardiac fibrosis after Ang II infusion compared with wild-type mice 88 , these mice were also found to be hypotensive in response to Ang II, and Ahr +/− mice were normotensive in response 89 . Furthermore, another study showed that treatment with tryptophan supplementation during pregnancy protects adult rat offspring from hypertension programmed by maternal chronic kidney disease 90 , suggesting possible dietary intervention therapies against pathologies related to the interplay between AHR and renin-angiotensin signaling. Taken together with our findings, the current research suggests that endogenous AHR signaling may play a role in developing ‘heart failure’ states, and that mitigation of this signaling such as via TCDD in adults may give rise to a ‘compensated’ state of mild hypertrophy in response to Ang II in comparison to a ‘heart failure’ state in corn oil controls.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has poor solubility and is difficult to add to eye drops. The bioavailability of curcumin has been improved through the development of the curcumin derivative tetrahydrocurcumin (THC) [248]. The solubility, stability, and release rate of curcumin can also be controlled through the use and development of nanocarriers.…”
Section: Natural Antioxidant Therapy For Oxidative Stress-related Eye...mentioning
confidence: 99%
“…The oral administration of curcumin can relieve chronic diabetic macular edema and improve visual acuity [259]. The above reports demonstrate the therapeutic value of natural antioxidants in ophthalmic diseases [248,260].…”
Section: Natural Antioxidant Therapy For Oxidative Stress-related Eye...mentioning
confidence: 99%